THE ROLE OF ISLAMIC EKONOMICS IN REDUCING SOCIAL INEQUALITY: A LITERATUR REVIEW ON THE EFFECTIVENESS OF ISLAMIC FINANCIAL INSTRUMENTS IN SOCIAL DEVELOPMENT - Eko Muliansyah (Dinar : Jurnal Prodi Ekonomi Syariah, 2025)
Islamic economics has gained significant attention in recent years as a solution to address social inequality and promote sustainable development. Islamic finance, with its principles of social justice, equitable wealth distribution, and responsible management of natural resources, offers a unique approach to economic and social development. This literature review aims to explore the role of Islamic economics in reducing social inequality and the effectiveness of Islamic financial instruments in driving social development. Key instruments in Islamic economics, such as zakat, waqf, and Islamic banking, have proven effective in addressing poverty, promoting financial inclusion, and funding social programs and infrastructure development. This study employs a literature review methodology, gathering and analyzing various relevant sources, such as journal articles, books, and research reports, that discuss the application of Islamic economic principles, particularly zakat, waqf, and Islamic microfinance, in the context of poverty alleviation, welfare equality, and social development. The findings indicate that while Islamic financial instruments have great potential, their implementation still faces challenges related to uncoordinated management, infrastructure limitations, and socio-political barriers. Therefore, a more coordinated, integrated, and community-driven approach that considers local social and cultural contexts is necessary. The study also highlights the importance of increasing public awareness about the benefits of Islamic financial instruments in supporting sustainable social development.